Teaching Health Care in Virtual Space Best Practices for Educators in Multi-User Virtual Environments - Codier, Estelle (University of Hawai'i Press, 2016)
Teaching Health Care in Virtual Space is the first "how-to" manual for health educators on the instructional use of three-dimensional, computer-generated virtual environments, called "multi-user virtual learning environments" or MUVE. Dr. Estelle Codier has written a step-by-step handbook based on her experience supervising more than 400 learning activities in Second Life®. The book provides specific steps to assess instructional readiness and guidance for assessing student and class readiness. The text is accompanied by lively case studies of student learning illustrate the power of MUVE to transform health care education.The text includes an appendix of evaluation grids, grading matrices, syllabus descriptions, and detailed orientation materials for both faculty and students. While the sample learning activities were designed for nurses, instructors in other disciplines could easily adapt them for use in any MUVE setting.